The Cambridge Introduction to George Orwell / [electronic resource] - Rodden, John; Rossi, John (Cambridge : Cambridge University Press, 2012)
Arguably the most influential political writer of the twentieth century, George Orwell remains a crucial voice for our times. Known world-wide for his two best-selling masterpieces Nineteen Eighty-Four, a gripping portrait of a dystopian future, and Animal Farm, a brilliant satire on the Russian Revolution, Orwell has been revered as an essayist, journalist and literary-political intellectual, and his works have exerted a powerful international impact on the post-World War Two era. This Introduction examines Orwell's life, work and legacy, addressing his towering achievement and his ongoing appeal. Combining important biographical detail with close analysis of his writings, the book considers the various genres in which Orwell wrote: the realistic novel, the essay, journalism and the anti-utopia. Ideally suited for readers approaching Orwell's work for the first time, the book concludes with an extended reflection on why George Orwell has enjoyed a literary afterlife unprecedented among modern authors in any language.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).